Search for electroweak single-top-quark production in pp̄ collisions at √s = 1.96 TeV - Acosta, D; Adelman, J; Affolder, T; Akimoto, T; Albrow, MG; Ambrose, D; Amerio, S; Amidei, D; Anastassov, A; Anikeev, K; Annovi, A; Antos, J; et al. (2005)
We report on a search for standard model t-channel and s-channel single-top quark production in pp̄ collisions at a center of mass energy of 1.96 TeV. We use a data sample corresponding to 162 pb-1 recorded by the upgraded collider detector at Fermilab. We find no significant evidence for electroweak top quark production and set upper limits at the 95% confidence level on the production cross section, consistent with the standard model: 10.1 pb for the t-channel, 13.6 pb for the s-channel and 17.8 pb for the combined cross section of t- and s-channel. © 2005 The American Physical Society.